Perceived risk of metabolic syndrome and attitudes towards fat-modified food concepts among European consumers - O'Brien, Gerard (2012)
European consumer willingness to purchase fat-modified foods was surveyed as part of the LIPGENE study. Representative samples of consumers (n = 5967) were interviewed in six countries (France, Great Britain, Portugal, Germany, Poland, and Italy). Of these 2025 were considered as ''reporters'' who indicated having at least one of: high cholesterol; high blood pressure; central obesity; and/or high blood sugar. Perceived risk from these conditions was also assessed on a 10-point scale. Principal component analysis suggested that those who perceived themselves at greater risk of conditions associated with metabolic syndrome, and those who were reporters, more frequently indicated willingness to purchase ''healthy'' fat-modified food products. The most preferred 'vehicles' for fat modification were fish and cheese. Acceptance of fat-modified fish, red meat and cheese product concepts, both standard and GM was positively associated with perceived risk of conditions associated with metabolic syndrome. Over 20% of reporters were willing to purchase GM fat-modified fish and cheese products. Our results indicate that if standard and GM fat-modified food products can be shown to ameliorate the risks presented by conditions associated with metabolic syndrome, there is a ready market for such foods.